Bottom-up effects may not reach the top: the influence of ant-aphid interactions on the spread of soil disturbances through trophic chains - Lescano, María Natalia (2012)
Soil disturbances that increase nutrient availability may trigger bottom-up cascading effects along trophic chains. However, the strength and sign of these effects may depend on attributes of the interacting species. Here, we studied the effects of nutrient-rich refuse dumps of the leaf-cutting ant, Acromyrmex lobicornis, on the food chain composed of thistles, aphids, tending ants and aphid natural enemies. Using stable isotopes tracers, we show that the nitrogen accumulated in refuse dumps propagates upward through the studied food chain. Thistles growing on refuse dumps had greater biomass and higher aphid density than those growing in adjacent soil. These modifications did not affect the structure of the tending ant assemblage, but were associated with increased ant activity. In contrast to the expectations under the typical bottom-up cascade effect, the increase in aphid abundance did not positively impact on aphid natural enemies. This pattern may be explained by both an increased activity of tending ants, which defend aphids against their natural enemies, and the low capacity of aphid natural enemies to show numerical or functional responses to increased aphid density. Our results illustrate how biotic interactions and the response capacity of top predators could disrupt bottom-up cascades triggered by disturbances that increase resource availability.